Lycopodiaceae endémicas del Perú - León, Blanca (2006)
This family is recognized in Peru with three genera and 65 species (Øllgaard, 1994; Smith et al., 2005). Only the genus Huperzia includes seven endemics for the Peruvian flora. These species are mostly terrestrial plants occurring in Pluvial Montane Forest, Dry and Humid Puna, and Paramo regions. Two endemic species are found in protected areas.